Structural, magnetic and dielectric properties of terbium doped NiCoX strontium hexagonal nano-ferrites synthesized via micro-emulsion route. Issue 7 (15th May 2016) - Rehman, Javed; Khan, Muhammad Azhar; Hussain, Altaf; Iqbal, F.; Shakir, Imran; Murtaza, Ghulam; Akhtar, Majid Niaz; Nasar, Gulfam; Warsi, Muhammad Farooq
Abstract: Terbium (Tb) doped X-type hexagonal nano-ferrites Sr2 NiCoTb x Fe28− x O46 ( x =0.00, 0.05, 0.1, 0.15, 0.2) were synthesized via micro-emulsion route. Single phase X-type hexagonal structure was confirmed by X-ray diffraction (XRD) analysis. The crystallite size of the samples was found in the range of 15–25 nm. The bulk density and X-ray density were enhanced while porosity was reduced with the increased Tb 3+ contents. The development of hexagonal phase was investigated by thermogravimetric analysis. The fourier-transform infrared (FTIR) spectra revealed the formation of spectral bands (metal-oxygen stretching vibration) which confirmed the hexagonal ferrites. The dielectric constant has high value at low frequency and decreased with increased frequency. The dielectric loss is appreciably decreased by the Tb 3+ incorporation and resonance phenomenon occurred beyond 1.7×10 9  Hz. The saturation magnetization (76–54 emu/g) and remanance (27–21 emu/g) decreased while coercivity increased (610–747 Oe) by Tb 3+ -incorporation in Sr2 NiCoTb x Fe28− x O46 ferrite. The values of squareness ratio (0.35–0.39) indicated that Tb-doped samples are single domain while un-doped material is multi domains. These synthesized nano-sized hexagonal ferrites have potential applications in high frequency and recording media devices.